A descriptive study on selected female university students' use of men's wear-inspired clothing - Jocson, Maria Patricia S.
ABSTRACT This study is about the use of men's wear-inspired clothing by selected female students from different colleges of the University of the Philippines in Diliman. The study determined the relationship of the respondents' allowance and course programs in terms of their clothing preferences and the quantity of men's wear-inspired clothing that they have. It also identified which details in a garment make it more "masculine" or more" feminine." A descriptive study was conducted using purposive, quota sampling. Forty (40) respondents purposively selected from University of the Philippines Diliman filled in a survey questionnaire about their clothing preferences, clothing quantity and how they define a garment's "gender." Ten (10) respondents each were chosen from College of Business Administration, College of Engineering, College of Home Economics and College of Mass Communications. The study provided new research material for the topic of androgynous fashion. It provides an insight in relation to the selected respondents' perception on the masculinity or femininity of clothes. The study revealed that the amount of allowance of the respondents may be a factor in having the most number of men's wear-inspired pieces and that the course program of the respondents does not affect the respondents' clothing choices, quantity of clothing in terms of men's. Garments were considered by the respondents as "feminine" if there are more details, form-fitting, more use of colors, softer fabrics and more trimmings. Garments that were considered "masculine" by the respondents are those with simple designs, loose silhouette, more structured and have sharp lines.